Peran Etika Kerja Islam dalam Mempengaruhi Motivasi Intrinsik, Kepuasan Kerja dan Dampaknya terhadap Komitmen Organisasional (Studi Empiris pada Pondok Pesantren Modern di Banten) - Hidayat, Syamsul; Tjahjono, Heru Kurnianto (Akmenika, 2015)
Islamic work ethic is very important in improving the quality of human resources at the boarding schools in Banten. A lot of researches on ethics of Islam have been conducted, but still rarely carried out with the object of study in Islamic educational institutions. This study intends to reexamine the role of Islam in influencing the work ethic of intrinsic motivation, job satisfaction and its impact toward organizational commitment. The population in this study is all teachers who work at the boarding schools in Banten. 245 teachers gave answers to this research. Data were analyzed by using Structural Equation Modeling (SEM). The analysis showed five accepted hypothesis and one hypothesis is rejected, that is a negative influence and insignificant between job satisfaction and organizational commitment. The limitations and suggestions for future research are discussed in this study.